Dissociated prismatic loop punching by bubble growth in FCC metals - Miaomiao Jin (Nature Portfolio, 2021)
Abstract Materials performance can be significantly degraded due to bubble generation. In this work, the bubble growth process is elaborated in Cu by atomistic modeling to bridge the gap of experimental observations. Upon continuous He implantation, bubble growth is accommodated first by nucleation of dislocation network from bubble surface, then formation of dissociated prismatic dislocation loop (DPDL), and final DPDL emission in $$\langle 110\rangle$$ ⟨ 110 ⟩ directions. As the DPDL is found capable of collecting He atoms, this process is likely to assist the formation of self-organized bubble superlattice, which has been reported from experiments. Moreover, the pressurized bubble in solid state manifests the shape of an imperfect octahedron, built by Cu $$\{111\}$$ { 111 } surfaces, consistent with experiments. These atomistic details integrating experimental work fill the gap of mechanistic understanding of athermal bubble growth in Cu. Importantly, by associating with nanoindentation testings, DPDL punching by bubble growth arguably applies to various FCC (face-centered cubic) metals such as Au, Ag, Ni, and Al.